Performance of fibre reinforced clayey soil - Narayan, Sumesh; Prasad, Avneel; Goundar, Sahil Shanil; Nasrekani, Farid Mahboubi (Edelweiss Applied Science and Technology, 2025)
The perfect type of soil for construction purposes is rare to find. Thus, there is a need to stabilize these soils based on their requirements. When it comes to clayey soil, the situation is even more difficult compared to most other soils. Clayey soil is classified as expansive soil, which means it expands when it absorbs a lot of water and shrinks when it dries up. Clay soils also don’t have much shear strength and bearing capacity to hold up a structure without any treatment. Waste fibers are the best solution to this, especially here in the Pacific, where we have an abundant supply of coconut waste whose husks are fibrous and suitable for reinforcing soils upon treatment. This is not only an environmentally friendly way to stabilize clayey soil but also a cost-effective method. This study focused on reinforcing clayey soils with fibrous materials such as coconut husk (coir), bamboo fiber, jute, and nylon ropes, which are available locally. These fibers were both mixed as short fibers in the soil matrix and woven into geogrids using the fibers to improve strength. Soil was also aided with stabilization using cement and lime to see the difference between treated and untreated fiber-reinforced soil samples. It was found that the addition of bamboo short fibers at a 1% ratio was the most effective solution. It can be observed that the addition of 1% fibers does result in about a 35% improvement in bearing strength over unreinforced soil, with a maximum of 12.31 CBR achieved. Through the addition of 5% lime and 5% cement to fiber-reinforced samples, a maximum compressive strength of 2.46 MPa was achieved.